Pengaruh Merek Dan Gaya Hidup Terhadap Keputusan Pembelian Produk Pada Toko Celcius Kota Palopo - Andi Cinta Nafsari A.T; Andi.Muh Fajri; Aji Wikra (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
This study aims to analyze the influence of brand and lifestyle on product purchasing decisions at the Celcius Store in Palopo City. As a local fashion brand, Celcius strives to attract consumers, particularly young people, through a strong brand image and trendy product styles. However, the influence of brand appeal and consumer lifestyle on purchasing decisions remains unknown. This study used a quantitative approach with a survey method, distributing questionnaires to 100 respondents who had purchased Celcius products at least twice in the past three months. Data were analyzed using multiple linear regression using SPSS version 25. The results showed that both simultaneously and partially, brand and lifestyle variables significantly influenced purchasing decisions. Lifestyle variables had a more dominant influence than brand. These findings suggest that consumers consider a product's suitability to their lifestyle before making a purchase decision. Therefore, the Celcius Store needs to strengthen its brand image and align its product offerings with the lifestyle preferences of its target market.